A simple and fast flow injection amperometry for the determination of methimazole in pharmaceutical preparations using an unmodified boron-doped diamond electrode - Adison Meoipun; Kantima Kaewjua; Orawon Chailapakul; Weena Siangproh (International Association of Physical Chemists (IAPC), 2023)
In this work, an automated flow injection analysis (FIA) connected to a boron-doped diamond electrode (BDDE) was originally developed for the analysis of methimazole in pharmaceutical preparations. At a modification-free BDDE, methimazole was easilly oxidized. For the analysis of the mechanisms occurring at the electrode surface, cyclic voltammetry was employed to evaluate the impact of fundamental experimental parameters, such as pH and scan rate, on the BDDE response. For the quantitative detection, the FIA amperometric approach was constructed and used as a fast and sensitive method. The suggested approach provided a broad linear range of 0.5-50 µmol/L and a low detection limit of 10 nmol/L (signal-to-noise ratio = 3). Furthermore, the BDDE was successfully utilized to quantify methimazole in genuine samples from a variety of medicines, and its performance remained steady after more than 50 tests. The findings of amperometric measurements exhibit excellent repeatability, with relative standard deviations of less than 3.9 and 4.7 % for intra-day and inter-day, respectively. The findings indicated that, compared with traditional approaches, the suggested method has the following advantages: quick analysis time, simplicity, highly sensitive output, and no need for complicated operational processes.